Constructing Meaning Through Speech: A Linguistic Case Study of an Indonesian Child’s Language Acquisition (PANOPTICON: Journal of English Studies, 2025)
This case study investigates early language acquisition in a four-year-old Indonesian child by analyzing her spontaneous speech within a psycholinguistic framework. Utilizing naturalistic data collected from two audio recordings of child–adult interaction, the study focuses on three core linguistic domains: phonology, morphology, and semantics. Through a qualitative descriptive approach and content analysis, the research identifies systematic phonological processes such as substitution (e.g., /r/ realized as /l/), productive morphological usage including compound numerals and possessive affixation, and emergent semantic constructions involving narrative structure, emotional vocabulary, and abstract concepts like time, negation, and causality. The findings reveal that the child's speech patterns reflect age-appropriate developmental milestones and align with established psycholinguistic norms. Furthermore, the study highlights the critical role of social interaction and contextual conversation in facilitating language growth. By documenting linguistic behaviors in an Indonesian context, this research offers culturally specific insights that enrich the global understanding of language development. The study underscores the importance of naturalistic observation in capturing children’s cognitive strategies and supports its continued use in early language research